Decolonizing democracy transforming the social contract in India - Keating, Christine (University Park Pennsylvania State University Press, 2011)
"Analyzes the movement for Indian independence, the framing of the Indian Constitution, and contemporary contestations over women's legal and political status as crucial moments of transition in which feminist and other progressive activists in India have challenged racialized and gendered underpinnings of democracy's social contract"--Provided by publisher.
Keywords: Women's rights -- India; Women -- Legal status, laws, etc. -- India; Feminism -- India; Constitutional history -- India; Social contract